Mercado das letras, mercado dos homens (Revista de História Regional, 2008)
In the 19th century, the fluminense press was the fate of many men of letters, whom had intended to get prestige and visibility from the reading audience. It was under this publishing media, characterized by the ephemeral, in which many writers acted and were, afterwards, consecrated by the History of Brazilian Literature. From this, the present article intends to map the presence of those men in the press, several of them being critics and novelists, pointing out the relationships they structured in this medium. It intends also to evoke the role those connections had in releasing the national literary production of the 1800s